Bioinformatics Domain Structure Prediction and Homology Modeling of Human Ryanodine Receptor 2 - Bauerová-Hlinková, V.; Bauer, J.; Hostinová, E.; Gašperík, J.; Beck, K.; Borko, Ľ.; Faltínová, A.; Zahradníková, A.; Ševčík, J. (IntechOpen, 2011)
None